Sustainable shared mobility in depopulated Japan: a case of Teshio, Hokkaido. - Uchiyama, Yosuke (Japan Forum, 2026)
Legal restrictions and pressure from the taxi industry have hindered the development of private vehicle paid passenger transport (ride-hailing) in Japan. In a super-ageing society facing depopulation, many regions struggle to maintain adequate transport infrastructure. The issue of legality regarding remuneration remains a significant barrier to ensuring sustainable door-to-door transport in depopulated areas. In April 2024, the Japanese government partially lifted the ride-hailing ban, which was accompanied by the deregulation of the Road Transportation Act and related policies. This study examines institutional changes and their impact on sustainable carpooling projects in depopulated areas before and after deregulation, using Teshio in Hokkaido as a case study. Employing narrative analysis, the study integrates longitudinal interviews with a Teshio Town official, exchanges with transport experts, and extensive secondary data. The findings reveal that the partial lifting of the ban is unlikely to directly address the challenges of sustainable carpooling projects, as it remains limited under the exceptions of the Road Transportation Act. The pioneering experience of Teshio highlights the practical regulatory adjustments necessary for developing a Japanese-style ride-hailing framework tailored to local needs.